OPTIMIZATION OF NARRATIVE WRITING LEARNING THROUGH COMMUNICATIVE MEDIA IN DEAF STUDENTS IN GRADE VII JUNIOR HIGH SCHOOL - Sriwidiastuty, Asi; Rokhman, Fathur; Wagiran, Wagiran; Hartono, Hartono (Journal of Social Science, 2024)
Objective: This study aims to examine the optimization of serial image media as an effective communicative tool for enhancing narrative writing skills among deaf students, addressing the challenges posed by limited language development and auditory impairments. Methods: A literature review approach was employed, analyzing 15 peer-reviewed articles published between 2018 and 2024. Articles were identified using targeted keywords such as "Ability to Write with Serial Images in Deaf Students" and underwent a rigorous selection process including identification, screening, and feasibility testing. Data synthesis was conducted using a narrative method to group findings based on measured outcomes. Results: The findings indicate that serial image media significantly improve the writing skills of deaf students by fostering engagement, enhancing comprehension, and strengthening memory retention. Students exhibited greater enthusiasm and motivation when learning through visual aids, which facilitated a deeper understanding of narrative structures. Novelty: This research underscores the critical role of visual media as a tailored instructional strategy to overcome linguistic barriers in deaf education. The study contributes new insights into inclusive teaching practices by demonstrating the high effectiveness of serial image media in improving narrative writing skills. Implication: The results emphasize the need for educators to integrate visual tools into language learning curricula to support students with special needs and enhance classroom inclusivity.